Whole genome amplification of sodium bisulfite-treated DNA allows the accurate estimate of methylated cytosine density in limited DNA resources - Jonathan Mill; Simin Yazdanpanah; Eva Gückel; Sigrid Ziegler; Zachary Kaminsky; Arturas Petronis (BioTechniques, 2006)
Sodium bisulfite modification-based fine mapping of methylated cytosines represents the gold standard technique for DNA methylation studies. A major problem with this approach, however, is that it results in considerable DNA degradation, and large quantities of genomic DNA material are needed if numerous genomic regions are to be profiled. In this study, we examined whether whole genome amplification (WGA) techniques can be applied to sodium bisulfite-treated DNA and whether WGA would bias DNA methylation results. Sodium bisulfite-treated DNA was amplified using a standard WGA method: optimized primer-extension preamplification (PEP) with degenerate primers. Following the PCR of bisulfite-treated DNA, the DNA methylation profiles of specific DNA fragments were assessed using three approaches: (i) direct sequencing of the overall product; (ii) the sequencing of cloned PCR products; and (iii) methylation-sensitive single nucleotide primer extension (MS-SNuPE)—and compared with those obtained from bisulfite-treated DNA not subjected to WGA. Our data indicates that the DNA methylation profiles obtained from WGA of sodium bisulfite-treated DNA are consistent with those obtained from non-WGA DNA. The average difference in methylation percentage calculated from the two sets of template using MS-SNuPE was 4%. If our results are replicated on other genomic loci, WGA may become a useful technique in DNA methylation studies.